Educational Leadership in Aragon’s State Schools - Andrés Rubia, Fernando (Avances en Supervisión Educativa, 2024)
The article makes a first approximation to the current situation of studies on educational leadership in the Spanish and Aragonese spheres, pointing out in particular its shortcomings, as it has not acquired a position of relevance either in the public educational policies of the last decades or in the different laws that have been approved that regulate the right to education. Below, and based on a study developed by the School Council of Aragon, with directors of different types of educational centers, some of the most outstanding results are shown. This is a study carried out with qualitative and quantitative techniques that collects the opinion of Aragonese directors on their performance, emphasizing their vision of educational leadership. The conclusions include different proposals with the aim of promoting educational leadership in Aragon.
Keywords: Educational leadership; educational Improvement; leadership for learning; distributed leadership; leadership for social justice; Aragón